The role of perceived discrimination in mediating the relationship between minority status and psychotic symptoms in a community sample - Hermanto, Eko; Asih, Sali Rahadi; Jaya, Edo Sebastian (Konselor, 2019)
Minority groups have been found to be at higher risk of developing psychotic symptoms, but the underlying mechanism is yet to be established. This study aims to determine the mechanism that underlies the relationship between minority status and psychotic symptoms, investigating the role of perceived discrimination as a mediator. We assessed 387 participants from a community sample in Indonesia using the Community Assessment of Psychotic Experiences for psychotic symptoms, surveys adapted from the NEMESIS study for minority status and perceived discrimination, and controlled for depression with the Patient Health Questionnaire-9. Mediation analysis was conducted, which showed that perceived discrimination fully mediated the relationship between minority status and positive psychotic symptoms, but not negative psychotic symptoms. This finding supports the social defeat hypothesis, which states that social stressors lead to positive psychotic symptoms due to dopamine dysregulation. However, further research is required to illustrate the association between social stressors and negative symptoms.